Salt stress on physiology, biometry and fruit quality of grafted Passiflora edulis (Bioscience Journal, 2020)
The production of grafted passion fruit is an alternative for plant adaptation to saline environments. The objective of this study was to evaluate the effect of salt stress on physiology, biometry and fruit quality of P. edulis grafted on Passiflora spp. The experiment was conducted in completely randomized design, in a 3 x 2 factorial scheme, corresponding to three species of Passiflora (P. edulis, P. gibertii and P. cincinnata) with P. edulis scion and two levels of irrigation water salinity (0.5 - control and 4.5 dS m-1), with four repetitions. Water salinity compromises gas exchanges (CO2 assimilation raste and transpiration) and physiological variables (total chlorophyll and total water consumption) in grafted P. edulis. The interaction between the factors (water salinity x species) compromised only the growth in plant height and number of leaves. In relation to the species, auto-grafted P. edulis stood out from the other species, with higher internal CO2 concentration, number of leaves, stem dry mass, peel thickness, total soluble solids (TSS) of the pulp and TSS/TA ratio (titratable acidity). Auto-grafted P. edulis under saline conditions develops vital mechanisms (TSS and TSS/TA), which attenuates the effects of salt stress on the physico-chemical quality of the fruits.